ANALYZING THE INFLUENCE OF JOB STRESS ON EMPLOYEE PRODUCTIVITY AT PT. BANK TABUNGAN NEGARA (PERSERO) TBK MANADO - Timah, Nygel Eka (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Nowadays a lot of new companies established so as to make each company further enhance the role of employee. The data survey of Regus in Indonesia is more than half of workers in Indonesia (64%) said that their stress levels increased compared to last year. Job stress is a part that is always related to the employee and the productivity that can decrease employee productivity in the workplace. Stress affects the employee productivity because it is a serious problem in the world of work, and becomes one important problem faced by employees. The problem of job stress can result from the same person within the scope of their workers or the organization. This is a quantitative research that associative with multiple linear regression analysis technique. The population in this study is the employees at PT. Bank Tabungan Negara (Persero) Tbk Manado, and the respondents are 30 people. This study may imply that the contribution of Lack of Financial Reward, Inflexibility in work hours, and Low control over the work environment on Employee Productivity of 92.3% while the remaining 7.7% is affected by other variables not examined in this study, and For PT. Bank Tabungan Negara (Persero) Tbk, Manado In managerial role should consider about the Job Stress since it is the most crucial part of the company and how companies can provide encouragement and motivation by providing financial rewards for employees who have good work. Keywords: job stress, employee productivity